THE IMPACT OF VISUAL MERCHANDISING ON IMPULSIVE BUYING AT AVENUE STORE MANADO TOWN SQUARE - Sendu, Gwendolyn; Lapian, Joyce S.L.H.V.; Mangantar, Marjam (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Visual merchandising plays important role in retail stores as a tool being used by retailer to extend and increase the sales volume over their competitors, to be prominent in the market and become a source of attraction for the customers. Visual merchandising elements such as window display, mannequin display, floor merchandising, and promotional signage serve as the strong stimuli to impulsive buying that attract, engage, and motivate customer to buy. The purpose of this study is to analyze the impact of visual merchandising toward consumer’s impulsive buying on Avenue store in Manado Town Square at Manado. This study uses quantitative research method in cross sectional study and Multiple Linear Regression as the tool for analysis. The study’s findings reveal that four elements of visual merchandising have positive relationship and significant influence on impulsive buying behavior. From this finding, the management consider factors to attract customer’s attention, interest, desire, and action by frequently change of window display and mannequin display, rearrange the merchandise fixtures and props as well as the corridor space for customer’s comfortable and experience, and to increase promotional events that notice to customer’s interest by providing effective information on promotional messages and price discounts in the promotional signage. Keywords: visual merchandising, window display, mannequin display, floor merchandising, promotional signage, impulsive buying.